2018
DOI: 10.1007/s00894-018-3753-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the structural properties of the active conformation BTL2 of a lipase from Geobacillus thermocatenulatus in toluene using molecular dynamic simulations and engineering BTL2 via in-silico mutation

Abstract: The discovery or development of thermoalkalophilic lipases that show high levels of catalytic activity in organic solvents would have important industrial ramifications. However, this goal is yet to be achieved because organic solvents induce structural changes in lipases that suppress their catalytic abilities. A deep understanding of these structural changes to lipases in the presence of organic solvents is required before strategies can be devised to stop them from occurring. In this work, we investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The decreases in monomer conversions may be resulted from inefficient enzyme-solvent interactions or water incorporated from atmosphere. It is known that, lipases catalyze esterification and transesterification reactions in hydrophobic organic solvents, whereas they catalyze hydrolysis in aqueous media [19]. Additionally, polydispersity indexes were measured around 1.5 for both two immobilized CALB preparations by GPC analysis.…”
Section: Synthesis Of Poly(δ-valerolactone) Homopolymers and Their Spmentioning
confidence: 96%
“…The decreases in monomer conversions may be resulted from inefficient enzyme-solvent interactions or water incorporated from atmosphere. It is known that, lipases catalyze esterification and transesterification reactions in hydrophobic organic solvents, whereas they catalyze hydrolysis in aqueous media [19]. Additionally, polydispersity indexes were measured around 1.5 for both two immobilized CALB preparations by GPC analysis.…”
Section: Synthesis Of Poly(δ-valerolactone) Homopolymers and Their Spmentioning
confidence: 96%
“…Particularly, the use of an apolar organic solvent (toluene) has been reported to increase BTL2 rigidity, as deduced from molecular dynamics simulations at temperatures as high as 450 • K (176.85 • C) [72], without observing any tendency for the lid to open. These same authors described that either inserting a thin layer of water around the enzyme or promoting a single point mutation (G116P) would be required for retaining activity in acyl-transfer processes [72].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the use of an apolar organic solvent (toluene) has been reported to increase BTL2 rigidity, as deduced from molecular dynamics simulations at temperatures as high as 450 • K (176.85 • C) [72], without observing any tendency for the lid to open. These same authors described that either inserting a thin layer of water around the enzyme or promoting a single point mutation (G116P) would be required for retaining activity in acyl-transfer processes [72]. Additionally, another very recent study confirmed the reduced flexibility of BTL2 in nonpolar organic solvents, using molecular dynamics on toluene and cyclohexane, and thus confirming the enhancement of thermostability of BTL2 in the presence of these type of solvents [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, for BTL2 it has been reported, based on molecular dynamics simulation, how the use of an apolar organic solvent (toluene) made the lipase structure more rigid, even in simulations carried out at 450°K (176.85°C) [90], without observing any tendency for the lid to open, and claiming that either inserting a thin layer of water around the enzyme or promoting a single point mutation (G116P) would be required for retaining activity in acyl-transfer processes [90]. Additional, another very recent study confirmed the reduced flexibility of BTL2 in non-polar organic solvents, using molecular dynamics on toluene and cyclohexane, and thus confirming the enhancement of thermostability of BTL2 in the presence of this type of solvents [53].…”
Section: Discussionmentioning
confidence: 99%